Respuesta :

Answer:

2x + 3y - 4 = 0

Step-by-step explanation:

Equation of the line → 2x - 3y + 4 = 0

3y = 2x + 4

y = [tex]\frac{2}{3}x+\frac{4}{3}[/tex]

Slope of this line 'm' = [tex]\frac{2}{3}[/tex]

y-intercept of this line → y = [tex]\frac{4}{3}[/tex] Or [tex](0, \frac{4}{3})[/tex]

Let the equation of the line is,

y = m'x + b'

By the property of perpendicular lines,

m × m' = -1

[tex]\frac{2}{3}\times m'=-1[/tex]

m' = [tex]-\frac{3}{2}[/tex]

Equation of the perpendicular line will be,

y = [tex]-\frac{3}{2}x+b'[/tex]

Since this line passes through [tex](0, \frac{4}{3})[/tex],

[tex]\frac{4}{3}=-\frac{3}{2}\times 0+b'[/tex]

b' = [tex]\frac{4}{3}[/tex]

Therefore, equation of the perpendicular line will be,

y = [tex]-\frac{2}{3}x+\frac{4}{3}[/tex]

3y = -2x + 4

2x + 3y - 4 = 0

ACCESS MORE